Design and Analytical Evaluation of an Immunoassay for Long Forms of Cardiac Troponin T - Aalto, Rami; Lahtinen, Akseli; Airaksinen, K. E. Juhani; Vasankari, Tuija; Hellman, Tapio; Koskimäki, Laura; Wittfooth, Saara (Oxford University Press, 2026)
Background
Cardiac troponins (cTn) are used as diagnostic biomarkers of acute myocardial infarction (MI), but elevated levels of cTn can also be observed in other conditions. We report here the design and analytical evaluation of an immunoassay that targets intact and mildly fragmented forms of cardiac troponin T (referred to as long cTnT), which has been shown to better differentiate between MI and end-stage renal disease than the current Roche Elecsys® high sensitivity cTnT assay.
Methods
The long cTnT assay was evaluated for analytical characteristics. Serum and heparin plasma sample matrices were compared and the analyte stability was studied by storing endogenous long cTnT from samples of ST-segment elevation MI patients in heparin plasma or buffer at different temperatures and subjecting samples to freeze–thaw cycles. The correlation of long cTnT levels and time after MI symptom onset was also studied.
Results
The long cTnT assay achieved a limit of detection of 10.8 ng/L and a lower limit of quantitation (10% CV) of 30.8 ng/L. The response was linear from 5 to 5000 ng/L. Serum produced significantly lower results than heparin plasma. Endogenous long cTnT tolerated freeze–thaw cycles, but stability was compromised when stored at higher temperatures. The fraction of circulating long cTnT was highest during early hours of MI.
Conclusion
The long cTnT assay presented good analytical performance. Our results support using heparin plasma as the sample material and avoiding prolonged sample storing at room temperatures. Long cTnT fraction decreases in time after the onset of type 1 MI.